Penerapan Metode Fuzzy Time Series Cheng Pada Peramalan Inflasi di Indonesia - Putri, Ikfira Agustina; El Maidah, Nova; Ariful Furqon, Muhammad (Computer Engineering Departement, Universitas Komputer Indonesia, 2024)
Inflation is the increase in prices and goods in a certain period whose growth is always sought to remain low and stable in order to realize public welfare. High inflation fluctuations have a major influence on a country's economy, so forecasting is needed that can be used as a reference for the Government and Central Bank to prevent high inflation while maintaining price stability in the future. In addition, inflation forecasting can help economic actors in decision making. Forecasting can be done with various methods, one of which is Cheng's Fuzzy Time Series. The inflation data used in this study was obtained from the Bank Indonesia website from January 2003 to September 2023 with a monthly data period of 249 data. The prediction results for a 9-month period are 5.54% for the highest inflation and 2.92% for the lowest inflation. Based on the testing that has been done, the MAPE error value is 9.54% with a very good MAPE value category.